„Paradygmat poszlakowy” i problemy wnioskowania w badaniach archeologicznych - Tabaczyński, Stanislaw (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The purpose of the paper is to present some reflections about the methodological suggestions of Carlo Ginzburg, especially those published in his essay Spie. Radici di un paradigma indiziario including also the discussion that followed them in „Quaderni di Storia” (1980; 1981). Three main problems stressed in this debate seem to be of the particular interest for archaeologists; 1) the nature of historical cognition and the notion of „paradigma indiziario" as they have been conceived by Ginzburg; 2) the relationship between the „context of justification” and „context of discovery" and 3) finally the most important one, the role of the conjectural abduction or reasoning culminating in a probable hypothesis in the historical and archaeological inference. Contrary to Ginzburg – and it is the first point who opposes his „conjectural paradigm" to „Galileo's" one, the author directs attention to the arguments against such a radical distinction of the natural sciences versus social and historical ones. Practically all the problems of historical (and archaeological) cognition are at the same time problems of all cognition in general. It is true for exemple that historical and archaeological research procedures usually are postgnostic: the point is to find out causes of certain facts which we believe to be the effects, but as was formulated by J. Topolski „neither can history remain indifferent to the function of formulating laws, nor can other disciplines be indifferent to the postgnostic procedure". The most important however is the statement that in postgnostic procedure „we may speak about the knowledge of effects only in so far as we know the causes, because the concept of effect acquires meaning only when it is an element of the ordered pair: cause-effect". A caracteristic of the historical science based on the one segment only of this pair is in effect insufficiant and controversial. The second problem concers directly concepts and theoretical statements lying at the foundations of „New Archaeology” and research trends resulting from it or referring to its achievements. Contrary to Binford's neopositivist thesis, the „context of discovery" seems to constitute an integral part of the „context of justification". But the logic of discovery seems to be in the history, as in the others sciences, „still a grossly underdeveloped domain" and the emphasis upon verification rather than discovery constitues still ..a distortion of the actual emphases in the practice of science". It seems that the publications of Ginzburg and the debate following them despite certain reservation render services to a better cognition of the problem-solving process in the historical sciences. The third question, that's just the process of discovery described by H. A. Simon. It is „a process of selective trial and error, using heuristic rules derived from previous experience, that is sometimes successful in discovering means that are more or less efficacious in attaining some end" That process was called by Peirce „retroduction" or „conjectural abduction". This third type of reasoning has constituted recently the subject matter of certain methodological studies, it will be certainly also in future of great interest for archaeologists.